Indispensable! becoming the obvious choice in business and in life - Cottrell, David; Nix, Robert (McGraw-Hill, 2013)
Isn't it time you got the job you deserve? Your workplace transformation is about to begin! FACT: When opportunity knocks in the workplace, most people don't know how to seize it. This book will show you exactly how to spot--and master--your next great job opportunity. Are you ready to become the OBVIOUS CHOICE at promotion time? You can be. The good news? It's a lot easier than you think. Believe it or not, you already have the tools. Indispensable! teaches you how to use them to position yourself for job success, every time. From international bestselling author and leadership expert David Cottrell and sales guru Robert Nix comes the ultimate insider's guide for those who want to break through and control their professional destiny. In simple, clear language--featuring informative and relatable case studies--you'll discover how easy it can be to transform your on-the-job persona to become the person who succeeds first and fastest. No matter what your title is, you'll be equipped to navigate the trickiest workplaces and position yourself for growth at every turn. You'll put yourself in the spotlight and become the individual everyone else admires and wants to be. Indispensable! demonstrates how to create and maintain your best image 24/7: how to project strength, smarts, competence, and leadership. It's an indispensable road map with superb strategies for how to: Assess your workplace persona and perception Formulate a goal-oriented action plan that works Incorporate behavior modification to transform yourself inside and outside of work Identify, set, and sustain measurable goals Optimize your organizational skills (while decluttering your life) Indispensable! is packed with tips on how to listen, how to put coworkers at ease, how to use humor to your advantage (and when to avoid it), how to participate at business functions, and how to cultivate a public persona and effortless demeanor that attracts others. PRAISE FOR INDISPENSABLE! " Indispensable! A powerful guide for all who want to become indispensable within their organization."--Marshall Goldsmith, author of What Got You Here Won't Get You There " Indispensable! is a little book full of big ideas that can be understood and applied by anyone-anyone, that is, who really wants to increase their value, their respectability, and the likelihood they will be promoted. Read this book and take the first step above average to Indispensable!" -- Ken Blanchard, coauthor of The One Minute Manager ...